2016
DOI: 10.1021/acs.energyfuels.6b01183
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Degree of Unsaturation on Combustion Efficiency and Flue Gas Emissions of Burning Five Refined Vegetable Oils in an Emulsion Burner

Abstract: This work presents experimental studies performed on a low-pressure auxiliary air fluid pulverization burner fueled with refined vegetable oils to research the impact of the fatty acid profile on combustion and regulated emissions. The vegetable oils used were coconut, palm, rapeseed, sunflower, and soya. First, the fatty acid profile and the degree of unsaturation of these vegetable oils were determined by high-resolution nuclear magnetic resonance spectroscopy. The physicochemical properties (density, kinema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…VOs are triacylglycerols whose fatty acids profile displays different substitution patterns with regard to length, degree of unsaturation and chain geometry of the hydrocarbon chains. The fatty acid composition of each VO is unique, affects the state of aggregation, and impacts the physical properties such as density, viscosity and heating value [23,[25][26][27][28]. As a result, fatty acid composition determines the VO's behaviour during the combustion process, as recently shown by [28]…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…VOs are triacylglycerols whose fatty acids profile displays different substitution patterns with regard to length, degree of unsaturation and chain geometry of the hydrocarbon chains. The fatty acid composition of each VO is unique, affects the state of aggregation, and impacts the physical properties such as density, viscosity and heating value [23,[25][26][27][28]. As a result, fatty acid composition determines the VO's behaviour during the combustion process, as recently shown by [28]…”
Section: Methodsmentioning
confidence: 92%
“…First, a descriptive study of the variables involved in the combustion process was Furthermore, high viscosity values give rise to poor fuel atomization, incomplete combustion and unburned hydrocarbon formation, which could explain the positive correlation between CxHy and viscosity. As regards the negative correlation between viscosity and the lower heating value (LHV), San José et al [23] observed that the LHV of several VOs, rich and poor in unsaturated fatty acids, increased as the DU (Table 2) increased, contrary to viscosity. In contrast, direct correlation between LHV and viscosity in FAMEs (biodiesel) has been established by some researchers [25][26][27][28] Due to the significance of most of the interaction effects, it is essential to analyse interaction plots (Figures 2-6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where, Cp g means specific heat of flue gases at constant pressure for flue gas temperature (kJ/kg fuel • • C), m 1 g mass of non-stoichiometric flue gas per kg of combustible. Both parameters were calculated as procedure described in [24,26]. t a and t g are combustion air temperature and flue gas temperature at output, in ( • C), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Both variables were measured directly in gas analyzer. In an effort to ensure the experimental results were obtained in the same facility operating conditions, a test method previously described by our research group was used [24]. Once the facility was put into a steady state with diesel, the burner operation parameters were established (fuel and air flow rates) and the facility was run with the VO pre-heated to 40 • C for about two minutes until steady state was reached.…”
Section: Introductionmentioning
confidence: 99%